(b + 1)(a - 2) - a - ab - 2 - 2b - 2 - 2b + ab + a - a + 2 + 2b - ab + 2b + ab + a + 2 == ab + a -2b -2 - a - ab - 2 - 2b - 2 - 2b + ab + a - a + 2 + 2b - ab + 2b + ab + a + 2 == ab - ab + ab - ab + ab + a - a + a + a - a -2b - 2b - 2b + 2b + 2b -2 - 2 - 2 + 2 + 2 == ab(1 - 1 + 1 - 1 + 1) + a(1 - 1 + 1 + 1 - 1) -2b(1 + 1 + 1 - 1 - 1) - 2(1 + 1 + 1 - 1 - 1) == ab(0 + 0 + 1) + a(0 + 2 - 1) -2b(2 + 0 - 1) - 2(2 + 0 - 1) == ab + a - 2b - 2 == a(b + 1) - 2(b + 1) = (b + 1)(a - 2)Ответ: (b + 1)(a - 2)